A bioinspired soft manipulator for minimally invasive surgery. (13th May 2015) - Ranzani, T; Gerboni, G; Cianchetti, M; Menciassi, A
Abstract: This paper introduces a novel, bioinspired manipulator for minimally invasive surgery (MIS). The manipulator is entirely composed of soft materials, and it has been designed to provide similar motion capabilities as the octopus's arm in order to reach the surgical target while exploiting its whole length to actively interact with the biological structures. The manipulator is composed of two identical modules (each of them can be controlled independently) with multi-directional bending and stiffening capabilities, like an octopus arm. In the authors' previous works, the design of the single module has been addressed. Here a two-module manipulator is presented, with the final aim of demonstrating the enhanced capabilities that such a structure can have in comparison with rigid surgical tools currently employed in MIS. The performances in terms of workspace, stiffening capabilities, and generated forces are characterized through experimental tests. The combination of stiffening capabilities and manipulation tasks is also addressed to confirm the manipulator potential employment in a real surgical scenario.